2008
DOI: 10.7202/018777ar
|View full text |Cite
|
Sign up to set email alerts
|

Recherche d’indicateurs de ruissellement et des risques d’érosion au moyen de tests d’infiltrométrie dans le bassin versant du Rhéraya (Haut-Atlas occidental, Maroc)

Abstract: L’objectif de ce travail est d’étudier les risques de ruissellement et d’érosion dans le bassin versant du Rhéraya (Haut-Atlas du Maroc) au moyen d’un irrigateur manuel à rampe sur 1 m2. Nous recherchons des indicateurs faciles à déterminer directement sur le terrain (états de surface du sol) ou à partir des tests en laboratoire (stabilité des agrégats, texture, matière organique), qui soient bien corrélés avec l’infiltrabilité et la turbidité issues des tests d’infiltrométrie. Pour les différents sols affleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For example, the plot recently plowed by cannabis in the spring, which has 89.24% of the open surfaces, recorded 70.4 mm/h -1 , while the low values of the final infiltration are recorded at the abandoned fields which have low proportions of open surfaces. For comparison, the influence of the opening surfaces on infiltrability, according to the tests carried out in the High Atlas, show a good positive correlation (R 2 = 0.77%) [Cheggour et al, 2008].…”
Section: Determining Factors Of Infiltration and Soil Lossmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, the plot recently plowed by cannabis in the spring, which has 89.24% of the open surfaces, recorded 70.4 mm/h -1 , while the low values of the final infiltration are recorded at the abandoned fields which have low proportions of open surfaces. For comparison, the influence of the opening surfaces on infiltrability, according to the tests carried out in the High Atlas, show a good positive correlation (R 2 = 0.77%) [Cheggour et al, 2008].…”
Section: Determining Factors Of Infiltration and Soil Lossmentioning
confidence: 98%
“…This has been observed by several researchers who have used the same simulation device in other regions, between covered areas and soil losses. In the Western Rif) the correlation is significant between detachability and covered surfaces (r = 0.88) [Zaher et al, 2021;Cheggour, 2008] in the High Atlas also showed a better positive correlation between the bare surface state parameter and solid transport (R 2 = 0.71%). Similarly [Nadoum K et al, 1995], indicate that increasing the quantity of residues left on the surface is very effective in controlling erosion.…”
Section: Determining Factors Of Infiltration and Soil Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…A., 2007). Pour les géomorphologues, la théorie davisienne et le modèle USLE de Wischmeier et Smith (1978) constituent les sources d'inspiration ayant conduit à l'adoption du bassin versant comme cadre idéal pour l'étude de l'érosion (Michel, 1973;Sogon, 1999;Cheggour, 2008;Cissokho, 2011; Sow S. A., 2017; Niang G. , 2021). Le bassin versant constitue ainsi l'unité géomorphologique par excellence pour mieux apprécier les différents facteurs et modalités qui déterminent le cycle de l'eau et le transport des sédiments (Fort, François, & Arnaud-Fassetta, 2015).…”
Section: Introductionunclassified